Association of Prediabetes and Type 2 Diabetes With Cognitive Function After Stroke: A STROKOG Collaboration Study. Issue 6 (June 2020) - Lo, Jessica W.; Crawford, John D.; Samaras, Katherine; Desmond, David W.; Köhler, Sebastian; Staals, Julie; Verhey, Frans R.J.; Bae, Hee-Joon; Lee, Keon-Joo; Kim, Beom Joon; Bordet, Régis; Cordonnier, Charlotte; et al.
Abstract : Background and Purpose—: Type 2 diabetes mellitus (T2D) is associated with cognitive impairment and an increased risk of dementia, but the association between prediabetes and cognitive impairment is less clear, particularly in a setting of major cerebrovascular events. This article examines the impact of impaired fasting glucose and T2D on cognitive performance in a stroke population. Methods—: Seven international observational studies from the STROKOG (Stroke and Cognition) consortium (n=1601; mean age, 66.0 years; 70% Asian, 26% white, and 2.6% African American) were included. Fasting glucose level (FGL) during hospitalization was used to define 3 groups, T2D (FGL ≥7.0 mmol/L), impaired fasting glucose (FGL 6.1–6.9 mmol/L), and normal (FGL <6.1 mmol/L), and a history of diabetes mellitus and the use of a diabetes mellitus medication were also used to support a diagnosis of T2D. Domain and global cognition Z scores were derived from standardized neuropsychological test scores. The cross-sectional association between glucose status and cognitive performance at 3 to 6 months poststroke was examined using linear mixed models, adjusting for age, sex, education, stroke type, ethnicity, and vascular risk factors. Results—: Patients with T2D had significantly poorer performance in global cognition (SD, −0.59 [95% CI, −0.82 to −0.36]; P <0.001) and in all domains compared with patients with normal FGL. There was no significant difference between impaired fasting glucose patients and those with normal FGL in global cognition (SD, −0.10 [95% CI, −0.45 to 0.24]; P =0.55) or in any cognitive domain. Conclusions—: Diabetes mellitus, but not prediabetes, is associated with poorer cognitive performance in patients 3 to 6 months after stroke. Abstract : Supplemental Digital Content is available in the text.